2022
DOI: 10.3390/nano12183201
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Curcumin-Capped Nanoparticle Synthesis in Cancer Therapy: A Green Synthesis Approach

Abstract: Cancer nanotherapeutics is an important field of research which utilizes nanomaterials as an approach to cancer therapy. Nano-mediated therapeutic delivery systems overcome the adverse side effects of traditional cancer treatment methods. Nanoparticles (NPs) are considered excellent tumor-targeting vehicles due to their compact and variable size, large surface area, ability to load several genes and drugs, and mediation of increased therapeutic payload uptake. Despite the rapid development of nanotechnology, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 143 publications
0
2
0
Order By: Relevance
“…Plant extracts are known to be generally well tolerated and generally nontoxic in models of healthy cells in two-dimensional culture [57]. In addition, in recent years, progress has been made to reduce the therapeutic dose and improve its ability to target tumor cells, mainly using nanoparticles loaded with compounds isolated from extracts [58][59][60][61][62]. On the other hand, it has been shown that these natural products are capable of reducing the side effects of chemotherapy and radiotherapy and the systemic toxicity derived from aggressive treatments [41].…”
Section: Discussionmentioning
confidence: 99%
“…Plant extracts are known to be generally well tolerated and generally nontoxic in models of healthy cells in two-dimensional culture [57]. In addition, in recent years, progress has been made to reduce the therapeutic dose and improve its ability to target tumor cells, mainly using nanoparticles loaded with compounds isolated from extracts [58][59][60][61][62]. On the other hand, it has been shown that these natural products are capable of reducing the side effects of chemotherapy and radiotherapy and the systemic toxicity derived from aggressive treatments [41].…”
Section: Discussionmentioning
confidence: 99%
“…(Table 1: Classification, sources, and functional properties of bioactive substances). As a safe and natural food additive with many sources and at low cost, active substances have a positive impact on a variety of diseases, such as diabetes [65,66], cancer [67], autoimmune diseases [68], cardiovascular diseases [69], and neurodegenerative diseases [70]. Curcumin is a polyphenolic substance extracted from the rhizomes of plants, such as ginger and araceae, and is a rare diketone compound in the plant kingdom [71].…”
Section: Origin Classification and Functional Properties Of Bioactive...mentioning
confidence: 99%
“…In comparison to free curcumin, nanostructured curcumin has a higher systemic bioavailability in the plasma and tissues, according to Zou et al [ 21 ]. Furthermore, compared to therapy with native curcumin, nanocurcumin has a 60-fold longer biological half-life and enhances in vivo absorption and dispersion [ 22 ]. Moreover, several formulations of nanoparticle-based curcumin were non-toxic in acute toxicity studies at doses equivalent to 2 g curcumin/kg of body weight.…”
Section: Introductionmentioning
confidence: 99%